Male infertility in a large industrial city: the role of chemical, physical and emotional factors - O. O. Lomeiko; Yu. M. Kolesnik; N. V. Avramenko (Zaporozhye State Medical University, 2018)
The problem of infertile marriages has worsened recently in the world. Today there are 60.0 to 80.0 million infertile couples, in 40.0% of cases married couples are infertile due to a man's fault. The aim of the work is to analyze specialized scientific literature for generalization of data on modern views on etiology and pathogenesis of male infertility in urbanization. Materials and methods. Available scientific sources over the past five years, devoted to the mechanisms of male infertility in urbanization are studied by the methods of overview, system and content analysis. The data of the world statistics are presented and the data of modern researches devoted to the influence of chemical, physical and emotional factors on the parameters of male infertility are analyzed. It is accentuated on active forms of oxygen and parameters that reflect the morphological and functional state of spermatozoa, as well as the problems of male infertility that need to be addressed. A number of other factors affecting male infertility have been analyzed, in particular: food factors in urbanization, the role of chemical compounds in the anthropogenic environment, the importance of emotional factors and the risk caused by physical factors. Conclusions. It has been confirmed that external conditions have a serious impact on the development of reproductive system disorders in men, although their causes and structure are still unclear, are controversial despite a convincing list of factors that interfere with spermatogenesis. Based on the sources studied, it can be argued that there is no single model of oppression of the male reproductive function that can explain pathogenetic changes in various components of the reproductive apparatus, depending on the direction and strength of the adverse factor. The creation of such a model will make it possible to approach the issue of prevention of reproductive disorders in a context of various external factors. To study the relationship between stress and the development of secondary infertility and subfertility in men, it is necessary to study further the patterns obtained on the basis of clinical-laboratory, statistical and epidemiological studies.